Mitotic Index is an Independent Predictor of Recurrence‐Free Survival in Meningioma. (29th October 2014) - Olar, Adriana; Wani, Khalida M.; Sulman, Erik P.; Mansouri, Alireza; Zadeh, Gelareh; Wilson, Charmaine D.; DeMonte, Franco; Fuller, Gregory N.; Aldape, Kenneth D.
Abstract: While World Health Organization (WHO) grading of meningioma stratifies patients according to recurrence risk overall, there is substantial within‐grade heterogeneity with respect to recurrence‐free survival (RFS). Most meningiomas are graded according to mitotic counts per unit area on hematoxylin and eosin sections, a method potentially confounded by tumor cellularity, as well as potential limitations of accurate mitotic figure detection on routine histology. To refine mitotic figure assessment, we evaluated 363 meningiomas with phospho‐histone H3 (Ser10) and determined the mitotic index (number of mitoses per 1000 tumor cells). The median mitotic indices among WHO grade I (n = 268), grade II (n = 84) and grade III (n = 11) tumors were 1, 4 and 12. Classification and regression tree analysis to categorize cut‐offs identified three subgroups defined by mitotic indices of 0–2, 3–4 and ≥5, which on univariate analysis were associated with RFS ( P  < 0.01). In multivariate analysis, mitotic index subgrouped in this manner was significantly associated with RFS ( P  < 0.01) after adjustment for Simpson grade, WHO grade and MIB‐1 index. Mitotic index was then examined within individual WHO grade, showing that for grade I and grade II meningiomas, mitotic index can add additional information to RFS risk. The results suggest that the use of a robust mitotic marker in meningioma could refine risk stratification.